2020
DOI: 10.1007/s12325-020-01288-z
|View full text |Cite
|
Sign up to set email alerts
|

New Therapeutic Strategy and Innovative Lubricating Ophthalmic Solution in Minimizing Dry Eye Disease Associated with Cataract Surgery: A Randomized, Prospective Study

Abstract: Introduction: To evaluate the effects of a new lubricating, antioxidant solution (VisuEvo Ò) on dry eye disease (DED) in patients undergoing cataract surgery. Methods: Patients requiring cataract surgery with either healthy ocular surface or mild DED (tear break-up time, TBUT [ 7, Schirmer I test [ 15 mm/5 min) were enrolled in this multicenter, open-label, randomized, prospective study. Scheduled visits were 2 weeks before surgery (screening), day of surgery (V0), week 1 (V1), and 2 (V2) after surgery. VisuEv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 28 publications
2
24
1
Order By: Relevance
“…In our study, similarly to previous reports, 1,3,4,10,11 we found an increase of DED symptoms and an impairment of tear film stability, evaluated using BUT, especially in the group which did not receive the HPG/HA solution.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In our study, similarly to previous reports, 1,3,4,10,11 we found an increase of DED symptoms and an impairment of tear film stability, evaluated using BUT, especially in the group which did not receive the HPG/HA solution.…”
Section: Discussionsupporting
confidence: 91%
“…The changes in ocular signs and symptoms of DED during the study period were generally lower than in other reports, 1,3,4,11 in the group not treated with artificial tears as well: a possible cause is the inclusion of patients without pre-existing dry eye or risk factors.…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…The use of these eyedrops is associated with epithelial toxicity and worsening of goblet cell density. Therefore, in cases of postoperative DED, epitheliotoxic antibiotics should be avoided or used with caution and/or for a short duration [ 51 , 65 ]. In case of severe inflammation of the ocular surface, more aggressive treatment, including pulse topical steroid therapy or even topical immunomodulatory drugs, can be considered [ 37 , 66 ].…”
Section: Postoperative Managementmentioning
confidence: 99%
“…When the tear secretion volume is too high and the drainage is insu cient, the tear storage is on the high side; conversely, when the tear secretion is insu cient and the drainage is suitable, the tear storage is low; nally, when the tear secretion is insu cient and the drainage is insu cient, the tear storage may be normal [10,11,12]. SIt is a typical quantitative method for determining the composition of tear uid samples and can re ect the basic secretion of tears, and SIt is also a common detection index for patients with dry eyes [13,14].…”
Section: Discussionmentioning
confidence: 99%